International standard cost model manual: measuring and reducing administrative burdens for businesses - Standard Cost Model Network (SCM Network, 2005)
"The Standard Cost Model (SCM) is today the most widely applied methodology for measuring administrative costs. The SCM methodology is an activity-based meas-urement of the businesses' administrative burdens making it possible to follow the development of administrative burdens. At the same time the results from the SCM measurements are directly applicable to governments' simplification work, in that the results show the specific regulation and its details which are especially burdensome for businesses."